Fitness in Naturally Occurring and Restored Populations of a Grassland Plant Lychnis flos‐cuculi in a Swiss Agricultural Landscape. Issue 1 (11th April 2013) - Aavik, Tsipe; Bosshard, Daniel; Edwards, Peter J.; Holderegger, Rolf; Billeter, Regula
Abstract Wildflower seed mixtures are widely used for restoration of grasslands. However, the genetic and fitness consequences of using seed mixes have not been fully evaluated. Here, we studied the role of genetic diversity, origin (commercial regional seed mixtures, natural populations), and environmental conditions for the fitness of a grassland species Lychnis flos‐cuculi. First, we examined the relationship between genetic diversity, environmental parameters, and fitness in sown and natural populations of this species in a Swiss agricultural landscape. Second, we established an experiment in the study area and in an experimental garden to study the implications of local adaptation for plant fitness. Third, to examine the response of plants to different soil properties, we conducted an experiment in climate chambers, where we grew plants from sown and natural populations of L. flos‐cuculi as well as from seed suppliers on soils with different nutrient and moisture content. We detected no significant effect of genetic diversity on the fitness of sown and natural populations. There was no clear indication that plants from natural populations were better adapted to local environment than plants from sown populations or seed suppliers. However, plants of natural origin invested more into generative reproduction than plants from sown populations or seed suppliers. Furthermore, in the climate chamber, plants originating from natural populations tended to flower earlier. Our results indicate that using nonlocal seeds for habitat recreation may influence restoration success even if the seeds originate from the same seed zone as the restored site.